STRATEGI PENYUSUNAN KOMODITAS UNGGULAN DAERAH - Sugiyanto, Catur (Journal of Indonesian Economy and Business, 2007)
This paper evalutes the determination of competitive products implemented by localgovernment. We use the five aspects of business feasibility and the Revealed ComparativeAdvantages (RCA) analysis. The five aspects include marketing, financial, technique andproduction, management and legal, and social and environmental aspects. The RCAmesures comparative advantages of a product in a region in compare to its competitorwithin the same province. The paper found the competitive product selection implementedby the local government are not always inline with the five aspects of business feasibilityand the RCA. The use of the 5 aspects can help the banking sector to finance thecompetitive products and the use of the RCA can increase the possibility of the sector tohelp solving the local economic problems.Keywords: Komoditi Unggulan, RCA, MFEP, Location Quotion, Jawa Tengah